Relationship between joint attention and vocabulary development in Spanish children with Down syndrome - Galeote, Miguel; Checa, Elena; Sánchez, Concepción; Gamarro, Antonio (Revista de Investigación en Logopedia, 2013)
Joint attention (JA) has been regarded as a pre-requisite for language development. Curiously, JA has not been widely studied in children with Down syndrome (DS). Moreover, the research carried out does not show very clear results. Our aim is to evaluate the relationship between JA and vocabulary development in a wide sample of children with DS. A total of 131 children with DS and 131 children with typical development took part in the study, aged between 8 and 29 months of mental age. An adapted version for children with DS of MacArthur-Bates Communicative Development Inventory was used. Items related to JA were categorized according to the skill level. The results from both groups of participants were similar in all the variables examined. The most remarkable difference had to do with a better performance of children with DS in comprehension measures. No differences were found in protoimperative and protodeclarative responses.